The Development of Online Training Modules and Internet of things on Vehicle Air Conditioner - Jaroenlap, Chalermphol; Sovajassatakul, Thanongsak (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 1 (2021): January - March 2021DO - 10.14456/nujst.2021.4, 2020)
The objectives of this study were the following: 1) to develop online training modules and use the internet of things(IoT)  to enhance technicians’ competency on fixing vehicle air conditioners; the modules were evaluated by 5 experts who were selected by purposive sampling and 2) to evaluate the effectiveness of the training modules and the IoT. The participants were 40 Toyota service center technicians selected by cluster random sampling. The statistics used for analysis were mean, percentage, and standard deviation. The tools used were the following: 1) Four training modules (25 sub-units) and the IoT; 2) an achievement test consisted of 3 parts and 40 questions; and 3) A test on repair practice consisted of 20 questions. The following results were obtained: 1) The training modules in combination with the IoT were rated as High quality ( = 4.45, S.D.= 0.47) and 2) The effectiveness of the training modules as shown by the results of the during-the-training test and after-the-training test were 84.63 : 87.71, exceeding the passing criterion of 80 : 80. The developed training course should benefit working technicians of every Toyota service center in Thailand in their diagnosis and repair of vehicle air conditioners. Keywords : Training Modules, Internet of Things, Problem-Based Learning, Online Training, Vehicle Air Conditioner